If it's not what You are looking for type in the equation solver your own equation and let us solve it.
16x+0.25(12-x)=0.43(-12)
We move all terms to the left:
16x+0.25(12-x)-(0.43(-12))=0
We add all the numbers together, and all the variables
16x+0.25(-1x+12)-(0.43(-12))=0
We add all the numbers together, and all the variables
16x+0.25(-1x+12)+5.16=0
We multiply parentheses
16x-0.25x+3+5.16=0
We add all the numbers together, and all the variables
15.75x+8.16=0
We move all terms containing x to the left, all other terms to the right
15.75x=-8.16
x=-8.16/15.75
x=-7.03448275862/13.5775862069
| x-(-0.07)=4.5 | | n+1/n^2+2n-3=n/n+3-1/n-1 | | 3y=36-6y | | t+1/2t-1=5/7 | | 35x+25=140x+175 | | 5y+3=5(4)-2(1) | | y/5+8=24 | | 12x-4=3x-2+6x | | 20x+60=40x+80 | | 100+x/5=-10x+-10x-1 | | -19+12x-10x=-18 | | 7.1x-4.7=62.3 | | (3x+8)^2=64 | | 28–x=3x | | .9(90)=20+16p | | 6x+1/2x+(-1/2)=-(1/2) | | 20+16p=81 | | 12x-34=8x+15 | | -5=n/3 | | (3x+8)2^=64 | | 2x+9+3x+3x=3x+1 | | 2x+9+3x+3x=2x+8 | | 2x+9+3x+3x=2x+7 | | 2x+9+3x+3x=2x+6 | | 2x+9+3x+3x=2x+5 | | 2x+9+3x+3x=2x+4 | | 2x+9+3x+3x=2x+3 | | 2x+9+3x+3x=2x+2 | | 2x+9+3x+3x=2x+1 | | 2x+9+3x+3x=1x+9 | | 2x+9+3x+3x=1x+8 | | 2x+9+3x+3x=1x+7 |